Corrigendum: Comparison of ultrasonography and fluoroscopy as guides for extracorporeal shock wave lithotripsy in nephrolithiasis patients: a systematic review (Faculty of Medicine Universitas Indonesia, 2022)
[This corrects the article DOI: 10.13181/mji.oa.226140]